Technical efficiency of FDI firms in the Vietnamese manufacturing sector - Duong Vu Hoang (Review of Economic Perspectives, 2016)
The study examines technical efficiency of Foreign Direct Investment (FDI) firms in the Vietnamese manufacturing sector by applying stochastic production frontier model and making use of cross-sectional data in the period 2009-2013. The average level of technical efficiency of FDI firms is about 60% and it is higher than that of domestic firms (including private firms and state-owned firms). In addition, the study also analyses correlation between technical efficiency of FDI firms and other factors. It finds that there are positive correlations between FDI technical efficiency and net revenue per labour, firm's age or export activities in 2013. However, the study is unable to find evidence of a relationship between FDI technical efficiency and infrastructure or firm's investment activities.
Keywords: 330; FDI; Stochastic production frontier; Technical efficiency; Vietnam